FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN USAHA MELALUI MEDIA ONLINE PADA MASA PANDEMI COVID-19 - Tiara Damayanti; Arsa; Anzu Elvia Zahara (Lembaga Pengembangan Kinerja Dosen, 2023)
Business success is a success that is obtained if the business has achieved its goals. Through this research, it is expected to find out the factors that influence business success through online media during the covid-19 pandemic at the Yuni Gallery Shop Sengeti Muaro Jambi and find out the positive effects obtained from the use of social media on the Yuni Gallery Shop Sengeti Muaro Jambi. The type of research in this thesis is field research, using qualitative research methods. The object of research used in this research is Yuni Gallery Shop Sengeti Muaro Jambi. From the results of the research conducted, it is shown that: The Yuni Gallery Shop has 10 factors that influence business success through online media. In addition, Yuni Gallery Shop utilizes social media to gain positive influence by introducing various products to increase sales, marketing and business revenue.